Analisis Keberlanjutan Dan Strategi Pengembangan Wisata Desa â€œEmbung Pedangâ€ Di Desa Kepohkidul - Novi Nostalgianti; Moh Khusaini; Rita Parmawati (Jurnal Penelitian Pendidikan IPA, 2024)
Tourism development in East Java is considered appropriate because it will have an impact on the economic activities of village communities. Kepohkidul Village, Kedungadem District, Bojonegoro Regency has a tourist attraction, namely "Embung Pedang". This research aims to find a tourism strategy for Embong Pedang, Kepohkidul Village. The method used is Multidimensional Scaling (MDS) analysis. The research was conducted in Kepohkidul Village, Kedungadem District, Bojonegoro Regency from October to November 2023. The resulting index value shows that each dimension calculated sequentially has various statuses, namely the ecological dimension which is very sustainable, the economic, social and infrastructure dimensions which are still not sustainable, and the institutional dimensions are considered poor or unsustainable. The conclusion is sustainability index are not yet optimal in terms of dimensions, the sustainability of tourism needs to be improved especially in technology adoption to increase tourism in the village of "Embung Pedang".